1978
DOI: 10.1021/ac50029a004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tris(2,2'-bipyridyl)ruthenium(II) derivatives by reverse phase paired-ion high performance liquid chromatography

Abstract: Reverse-phase paired-ion high performance liquid chromatography (HPLC) has been used to determine diester, monoester-monocarboxylate and dicarboxylate derivatives of tris(2,2'-bipyridyl)ruthenium(II) (Run(bpy)32+) which can be distinguished on the basis of water solubility and molecular charge. Positively charged surfactant ruthenium derivatives have been ion-paired with methanesulfonate anions in the aqueous tetrahydrofuran mobile phase while their water soluble analogues have been paired with n-heptanesulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 9 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Finally, in addition to the previously mentioned reasons, the lack of standard reference compounds has severely limited study of larger PAG. A number of these compounds have been synthesized over the years (12), and considerable data (principally UV and fluorescence spectra) exist in the literature, but most of the compounds themselves are not available.…”
Section: Effect Of Sodium Heptanesulfonate As Ion-pairingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in addition to the previously mentioned reasons, the lack of standard reference compounds has severely limited study of larger PAG. A number of these compounds have been synthesized over the years (12), and considerable data (principally UV and fluorescence spectra) exist in the literature, but most of the compounds themselves are not available.…”
Section: Effect Of Sodium Heptanesulfonate As Ion-pairingmentioning
confidence: 99%
“…Valenty and Behnken (12) recently reported the separation of various diesterand monoester-monocarboxylate and -dicarboxylate derivatives of tris(2,2,-bypyridyl)ruthenium(II) by reversed-phase, paired-ion chromatography (RPPIC). They obtained plate counts and resolution near the theoretical value expected for the column and similar to that obtained with organic solutes.…”
mentioning
confidence: 99%
“…The object of this work was to develop a sensitive and simple method based on ion-pair reversed-phase (IPRP) HPLC-spectrophotometric detection system for trace aluminum in serum. For the determination of trace-metal ions, RP-HPLC is a relatively new technique (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). It was found that RP-HPLC, especially without addition of the chromogenic reagent in the eluent, has a number of advantages over previously described methods, offering a high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…First, it does not require a suitable model to describe the migration behaviour and can be used readily to describe the migration behavior and can be used readily for more than one variable as compared to the window diagram technique (13,14). Compared with direct search techniques (15,16), the ORM scheme is more capable of locating the global optimum within the selected range of experimental conditions. Furthermore, only a small set of preplanned experiments need to be performed in the ORM procedure.…”
Section: Introductionmentioning
confidence: 99%
“…MH+ + 2H20 ^MH+(H20) + HzO (8) MH+(H20)" + 2H20 ^MH+(H20)"+, + H20 (9) These last reactions are readily reversible and under appropriate conditions can lead to the establishment of thermo-0002-7863/78 /1500-6559S01.00/0 chemical equilibrium among all or some of the ionic species present in the mass spectrometer ion source.8,9…”
Section: Introductionmentioning
confidence: 99%